Examining the Abrasion Behaviour of PA 66 Gears in Different Cycles - Rifat Yakut; Hayrettin Düzcükoglu (Advances in Materials Science and Engineering)
Gears made of plastic-based materials are anticorrosive, resistant to magnetic environments, and light and have pulse decay, low noise, and self-lubrication properties, and therefore their usage areas are widening every single day. In this experiment, the working conditions of 30% fibreglass PA 66 (PA 66 GFR 30) plastic material with PA 66 (PA 66 GFR 30) plastic material and AISI 8620 couple gear are observed. Usage of PA 66 GFR 30 material as gear material at 56.75 Nm constant load and 750 rpm, 1000 rpm, and 1500 rpm was analysed. The load capacity damage formation of the material was also analysed. The tooth surface temperature, corrosion depth of the tooth profile, tooth damage, and the tooth surface were examined with an scanning electron microscopy (SEM) and the corrosive behaviour of gears was analysed.